2022
DOI: 10.1111/anae.15756
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ultra‐low, low and high concentration local anaesthetic for labour epidural analgesia: a systematic review and network meta‐analysis

Abstract: Summary Lumbar epidural is the gold standard for labour analgesia. Low concentrations of local anaesthetic are recommended. This network meta‐analysis investigated whether further reducing the concentration of local anaesthetic can improve maternal and neonatal outcomes without compromising analgesia. We conducted a systematic search of relevant databases for randomised controlled trials comparing high (>0.1%), low (>0.08% to ≤0.1%) or ultra‐low (≤0.08%) concentration local anaesthetic (bupivacaine or equivale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 27 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…The study by Bader [ 7 ] showed that 0.125% bupivacaine combined with 5 μg/mL alfentanil in the clinical application of epidural labor analgesia had a rapid onset of action, definite effect and high patient satisfaction, but the concentrations of both local anesthetic and alfentanil were slightly higher than those in our study. Hallidy et al [ 13 ] showed that ultra-low concentration (≤ 0.08%) local anesthetic increased the likelihood of spontaneous vaginal delivery, reduced motor block and shortened the duration of the second stage of labor compared to high concentration local anesthetic. Therefore, in our study, 0.075% ropivacaine was used and none of the women experienced motor block.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Bader [ 7 ] showed that 0.125% bupivacaine combined with 5 μg/mL alfentanil in the clinical application of epidural labor analgesia had a rapid onset of action, definite effect and high patient satisfaction, but the concentrations of both local anesthetic and alfentanil were slightly higher than those in our study. Hallidy et al [ 13 ] showed that ultra-low concentration (≤ 0.08%) local anesthetic increased the likelihood of spontaneous vaginal delivery, reduced motor block and shortened the duration of the second stage of labor compared to high concentration local anesthetic. Therefore, in our study, 0.075% ropivacaine was used and none of the women experienced motor block.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that decreased uterine activity in the second stage of labor is responsible for the increased rate of assisted instrumental delivery and risk of a low 5 min Apgar score [35,36]. Another meta-analysis indicated that the lower total local anesthetic drugs dose, the lower the probability of assisted vaginal and cesarean delivery, and the lower incidence of Apgar <7 at 1 min, however, ultra-low and high doses of anesthetic drugs can significantly shorten the first stage of labor compared to low doses, but there is no significant difference on the second stage of labor [23]. Critically, we observed no significant differences in cesarean and forceps delivery rates between groups, suggesting that delivery modes were similar across groups and that experimental sufentanil doses had no impact on these rates.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between opioids' adverse effects and drug dose has been confirmed, so clinicians believe the drug dose needs to be strictly controlled to achieve good analgesic effects and to avoid or minimize adverse drug reactions [23]. Many factors can affect the dose of drugs in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The obvious questions are, if all delays and barriers to receiving an epidural in labour were removed what would, or should, the rate of epidural analgesia be? Evidence from other countries and from other centres in the UK suggests a much higher epidural rate than the 25% reported by Halliday et al [6]. Modifications of this model can also be used to explain some negative outcomes associated with ethnicity in the study by O'Carroll et al [7], and more generally in other work reporting disparities in outcomes in racial and ethnically marginalised groups [22].…”
Section: The Three Delays Model For Explaining Inequities In Labour E...mentioning
confidence: 91%